Osteopathic manipulative treatment: Facial muscle energy, direct MFR, and BLT procedure – for TMJ dysfunction - Nahian, Ahmed; Ünal, Mehmet; Jr, Jacob Mathew (My University, 2022)
The temporomandibular joint is pivotal towards mastication and vocalization. Dysfunction in this joint can occur with macrotrauma, microtrauma, or maladaptive behaviors. A myriad of treatment options exist, both invasive and noninvasive. This activity reviews the evaluation and treatment of temporomandibular dysfunction and highlights the osteopathic provider's role in evaluating and treating this condition utilizing muscle energy, myofascial release, and balanced ligamentous technique.
Keywords: Facial Muscle Energy; Direct MFR; BLT Procedure